099 A randomized factorial study to understand the components of behavioral sleep extension. (3rd May 2021) - Baron, Kelly; Trela-Hoskins, Sarah; Allen, Chelsea; Duffecy, Jennifer; Lincoln, Layla
Abstract: Introduction: Recent studies have demonstrated that behavioral sleep extension can increase sleep duration among short sleepers. However, little is known about the contribution of the intervention components. The goal of this study is to examine the effects of a fitbit and coaching on sleep extension in a behavioral sleep extension intervention. Methods: Participants included adults aged 25 to 65 years with sleep duration <7 hours who were randomized into one of four groups: self-management, Fitbit, coaching, or Fitbit + coaching. The self-management group did not receive any intervention materials. The other three groups received sleep educational materials emailed weekly. The coaching intervention (5-min telephone call) was delivered weekly for 6 weeks to the coaching and Fitbit+coaching groups to enhance motivation. Assessments were completed at baseline, post intervention (6 weeks), and 12-week follow- up. Participants completed self-report questionnaires and actigraphy at study visits. Results were analyzed using mixed models. Results: Enrollment and data collection were ended prematurely due to the COVID-19 pandemic. Participants included 32 adults (self-management n=8, coaching n=11, Fitbit n=11, and Fitbit+coaching n=8). Fitbit+coaching group increased hours of sleep by 0.62 h hours more (95% CI: 0.04, 1.20; p=0.047) than the self-management group between their first and second visit. Coaching and the Fitbit groups showed estimated improvements over the self-management group as well: 0.54 h and 0.39 h, respectively, though their differences were not found to be statistically significant (p=0.081 and p=0.20, respectively). At the 12-week follow-up visit, there were no statistically significant differences between groups but the Fitbit+coaching group did maintain their sleep improvement. Conclusion: These results suggest that sleep extension intervention components may affect the pattern of sleep changes, but more research is needed to refine and explore changes in sleep with behavioral interventions. Support (if any): R01NR018891